COVERAGE AND CAUSES OF MISSED ORAL POLIO VACCINE IN URBAN AND RURAL AREAS OF PESHAWAR - Naeem, Mohammad; Adil, Muhammad; Abbas, Syed Hussain; Khan, Muhammad Zia-ul-Islam; Naz, Syeda Maria; Khan, Ayasha; Khan, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2011)
Background: Poliomyelitis mainly affects children under five years of age. Pakistan is one of the few countries where wild polio is still endemic. The purpose of this study was to find out the coverage rate and factors associated with the failure of OPV in urban and rural areas of Peshawar. Methods: This cross-sectional study was conducted in Peshawar. Data was collected through random sampling in Peshawar University, Peshawar Saddar, Hashtnagri, Naway Kalay and Pawaka from 9th to 19th June 2010. A questionnaire was used to interview parents of 548 children, aged four years and below, about demographics, OPV vaccination status, reasons for missed vaccination and views on immunization and EPI staff. Forty workers from immunization staff were also interviewed through a separate questionnaire to find out factors associated with low OPV coverage. Chi-square test was used for statistical testing and p<0.05 was considered significant. Results: Only 64.2% children were completely vaccinated, 13.3 % not vaccinated at all, and 22.4% were incompletely vaccinated. The reasons for not vaccinating were lack of awareness (23.8%), family problem/mother busy (20.8%), centre too far (21.3%), wrong ideas (10.2%), fear of reaction (7.6%), child ill (5.6%) and miscellaneous causes (10.6%). The problems faced by the EPI staff were lack of awareness among people (32.5%), load shedding (20.0%), poor transport facilities (10.0%), unavailability of vaccines (10.0%) and insecurity (10.0%). Conclusion: Low vaccination coverage in Peshawar is mainly due to low awareness among people, poor economic conditions and poor salaries, insecurity and transport problems faced by the immunization staff. Keywords: OPV, Immunization, EPI, Polio